Miliary Tuberculosis in Immunocompromised Patient Induced by Imatinib and Steroid - Fermada, Randa; Fauzar, Fauzar; Kurniati, Roza; Wahid, Irza (Jurnal Kesehatan Andalas, 2021)
Miliary tuberculosis occurs due to the hematogenous spread of Mycobacterium Tuberculosis from the primary complex.  The use of steroid and cytotoxic drugs increases the incidence of miliary tuberculosis.  Typical manifestations of miliary tuberculosis is snowstorm appearance seen on chest x-ray and evidence of tuberculosis microorganism from the microbiological examination.  It has been reported a 33 years old male patient was admitted to the hospital due to breathlessness, chronic coughing, fever, anorexia, weight loss and night sweating with a "damp shadow sign".  Due to chronic myelogenous leukemia and autoimmune hemolytic anemia, the patient is known under imatinib and steroid therapy.  There was no specific sign found from the physical examination.  Chest x-ray showed snowstorm appearance.  The patient underwent GeneXpert MTB/RIF, with the result low MTB detected.  The patient was treated with a 2(HRZE)/4(HR) tuberculosis drugs regimen.  Imatinib and steroid therapy was discontinued.  2-4 weeks of steroid usage with a daily dose equivalent to prednisone 15 mg increases the risk of activating a latent tuberculosis infection.  Imatinib affects the response of T cells to Mycobacterium, thereby triggering tuberculosis reactivation.  In this case, the diagnosis has been made from typical manifestations of tuberculosis, snowstorm appearance from the chest x-ray, and low MTB detected from GeneXpert MTB/RIF.  It has been recommended to detect latent tuberculosis infection before using steroid and cytotoxic drugs.Keywords:  imatinib, miliary tuberculosis,  steroid